An equilibrium theory signature in the island biogeography of human parasites and pathogens. Issue 1 (5th November 2015) - Jean, Kévin; Burnside, William R.; Carlson, Lynn; Smith, Katherine; Guégan, Jean‐François
Abstract: Aim: Our understanding of the ecology and biogeography of microbes, including those that cause human disease, lags behind that for larger species. Despite recent focus on the geographical distribution of viruses and bacteria, the overall environmental distribution of human pathogens and parasites on Earth remains incompletely understood. As islands have long inspired basic ecological insights, we aimed to assess whether the microorganisms that cause human disease in modern times follow patterns common to insular plants and animals. Location: Global and regional. Methods: Relying on the publically accessible GIDEON database, we use the spatial distribution of nearly 300 human parasites and pathogens across 66 island countries and territories to assess the current predictive value of the 'equilibrium theory' of island biogeography. The relationships between species richness and (1) island surface area and (2) distance to the nearest mainland were investigated with linear regression, and ANCOVAs were used to test for differences in these relationships with respect to pathogen ecology and taxonomy. Results: Pathogen species richness increases with island surface area and decreases with distance to the nearest mainland. The effect of area is more than 10 times lower than that usually reported for macroorganisms, but is greater than the effect of distance. The strongest relationships are for pathogens that are vector‐borne, zoonotic (with humans as dead‐end hosts) or protozoan. Main conclusion: Our results support the basic predictions of the theory: disease diversity is a positive function of island area and a negative function of island isolation. However, differences in the effects of area, distance and pathogen ecology suggest that globalization, probably through human travel and the animal trade, has softened these relationships. Parasites that primarily target non‐human species, whose distributions are more constrained by island life than are those restricted to human hosts, drive the island biogeography of human disease.